On Atmospheric Energy Transport by Waves - Heiskanen, Tuomas Ilkka Henrikki (UiT The Arctic University of Norway, 2018)
Recently a new method, based on a Fourier decomposition in the zonal direction, for studying the atmospheric energy transport contribution by planetary and cyclone scale waves has been proposed. Recent studies based on this show that planetary waves contribute more than cyclone scale waves to the atmospheric energy transport into the Arctic. The planetary waves contribute to the Arctic amplification through latent heat transport, even when the total atmospheric energy transport is decreasing in model projections. However, the performance of the energy split method to capture transports by cyclone and planetary scale waves has not yet been evaluated. Here an attempt to evaluate the performance of the energy split method is presented. The energy split method is applied on synthetic data, where the wave structure and energy transport are known. This leads to a potential error in the energy split methods resolution of transport associated with synthetic isolated cyclones, transport is contributed to planetary waves in the Fourier spectra. When applied on atmospheric reanalysis data where only isolated cyclones are present in atmospheric state it is evident that more than 80% (70%) of the transport of dry static energy (latent heat) is contributed by planetary waves. From inspections of the vertically integrated energy transport field it is evident that the latent heat transport of cyclones is large compared to the climatology, which implies that there is a problem with the energy split method when the atmospheric state is characterized by an isolated cyclone scale wave, and that the error is especially important to consider for the latent heat transport into the Arctic. Further investigations are proposed to estimate the upper bound of the error introduced in the energy split method.